Non-Contrast Enhanced MR Angiography (NCE-MRA) of the Calf: A Direct Comparison between Flow-Sensitive Dephasing (FSD) Prepared Steady-State Free Precession (SSFP) and Quiescent-Interval Single-Shot (QISS) in Patients with Diabetes - Zhang, Na (PLoS One, 2015)
OBJECTIVES: To compare the image quality and diagnostic performance of two non-contrast enhanced MR angiography (NCE-MRA) techniques using flow-sensitive dephasing (FSD) prepared steady-state free precession (SSFP) and quiescent-interval single-shot (QISS) for the calf arteries in patients with diabetes. MATERIALS AND METHODS: Twenty six patients underwent the two NCE-MRA techniques followed by contrast-enhanced MRA (CE-MRA) of lower extremity on a 1.5T MR system. Image quality scores, arterial stenosis scores, signal-to-noise ratio (SNR), contrast-to-noise ratio (CNR), vessel sharpness, and diagnostic accuracy for detecting more than 50% arterial stenosis were evaluated and statistically compared using CE-MRA as the reference standard. RESULTS: All examinations were performed successfully. Of the total 153 calf arterial segments obtained in the 26 patients, FSD and QISS showed no significant difference in the number of diagnostic arterial segments (151 [98%] vs. 147 [96%], respectively, P>0.05). The image quality of FSD was higher than that of QISS in the peroneal artery and posterior tibial artery (P<0.05), but no significant difference in the anterior tibial artery (P>0.05). SNR and CNR of FSD were higher than those of QISS (P<0.01), while FSD showed comparable vessel sharpness compared with QISS (P>0.05). The time efficiency of SNR and CNR between FSD and QISS showed no significant difference when taking into account the times for FSD-related scout scans. There was no difference in sensitivity (95% vs. 93%, P>0.05) and negative predictive value (98% vs. 97%, P>0.05) between FSD and QISS for detecting stenosis greater than 50%. However, FSD showed higher specificities (99% vs. 92%, P<0.05) and diagnostic accuracy (98% vs. 92%, P<0.05) compared to QISS. CONCLUSION: Both FSD and QISS had similar high sensitivity and negative predictive value for detecting calf arteries with over 50% stenosis, but FSD showed slightly higher diagnostic specificity and better depiction of arterial lesions due to its isotropic submillimeter spatial resolution. QISS, being an easier to use and less time-consuming technique, could be a method of choice for rapid screening of arterial disease of the lower extremity.